Automated high-content imaging for cellular uptake, from the Schmuck cation to the latest cyclic oligochalcogenides - Martinent, Rémi; López-Andarias, Javier; Moreau, Dimitri; Cheng, Yangyang; Sakai, Naomi; Matile, Stefan (Beilstein Journal of Organic Chemistry, 2020)
Recent progress with chemistry tools to deliver into living cells has seen a shift of attention from counterion-mediated uptake of cell-penetrating peptides (CPPs) and their mimics, particularly the Schmuck cation, toward thiol-mediated uptake with cell-penetrating poly(disulfide)s (CPDs) and cyclic oligochalcogenides (COCs), here exemplified by asparagusic acid. A persistent challenge in this evolution is the simultaneous and quantitative detection of cytosolic delivery and cytotoxicity in a high-throughput format. Here, we show that the combination of the HaloTag-based chloroalkane penetration assay (CAPA) with automated high-content (HC) microscopy can satisfy this need. The automated imaging of thousands of cells per condition in multiwell plates allows us to obtain quantitative data on not only the fluorescence intensity but also on the localization in a very short time. Quantitative and statistically relevant results can be obtained from dose–response curves of the targeted delivery to selected cells and the cytotoxicity in the same experiment, even with poorly optimized cellular systems.
Keywords: automation; cell-penetrating peptides; cellular uptake; cytosolic delivery; cytotoxicity; high-content imaging; thiol-mediated uptake

(untitled) - Hatai, J.; Schmuck, C. (Acc. Chem. Res., 2019)

(untitled) - Ulrich, S. (Acc. Chem. Res., 2019)

(untitled) - Gasparini, G.; Bang, E.-K.; Montenegro, J.; Matile, S. (Chem. Commun., 2015)

(untitled) - Feener, E. P.; Shen, W. C.; Ryser, H. J. (J. Biol. Chem., 1990)

(untitled) - Méndez-Ardoy, A.; Lostalé-Seijo, I.; Montenegro, J. (ChemBioChem, 2019)

(untitled) - Benner, N. L.; McClellan, R. L.; Turlington, C. R.; Haabeth, O. A. W.; Waymouth, R. M.; Wender, P. A. (J. Am. Chem. Soc., 2019)

(untitled) - Webber, M. J.; Langer, R. (Chem. Soc. Rev., 2017)

(untitled) - Zhang, Y.; Qi, Y.; Ulrich, S.; Barboiu, M.; Ramström, O. (Mater. Chem. Front., 2020)

(untitled) - Andersen, K. A.; Smith, T. P.; Lomax, J. E.; Raines, R. T. (ACS Chem. Biol., 2016)

(untitled) - Hashim, P. K.; Okuro, K.; Sasaki, S.; Hoashi, Y.; Aida, T. (J. Am. Chem. Soc., 2015)

(untitled) - Murayama, T.; Masuda, T.; Afonin, S.; Kawano, K.; Takatani-Nakase, T.; Ida, H.; Takahashi, Y.; Fukuma, T.; Ulrich, A. S.; Futaki, S. (Angew. Chem., Int. Ed., 2017)

(untitled) - Herce, H. D.; Garcia, A. E.; Cardoso, M. C. (J. Am. Chem. Soc., 2014)

(untitled) - Bechara, C.; Sagan, S. (FEBS Lett., 2013)

(untitled) - Bode, S. A.; Wallbrecher, R.; Brock, R.; van Hest, J. C. M.; Löwik, D. W. P. M. (Chem. Commun., 2014)

(untitled) - Du, S.; Liew, S. S.; Li, L.; Yao, S. Q. (J. Am. Chem. Soc., 2018)

(untitled) - Whitney, M.; Savariar, E. N.; Friedman, B.; Levin, R. A.; Crisp, J. L.; Glasgow, H. L.; Lefkowitz, R.; Adams, S. R.; Steinbach, P.; Nashi, N.; Nguyen, Q. T.; Tsien, R. Y. (Angew. Chem., Int. Ed., 2013)

(untitled) - Schmidt, D.; Jiang, Q.-X.; MacKinnon, R. (Nature, 2006)

(untitled) - Derivery, E.; Bartolami, E.; Matile, S.; Gonzalez-Gaitan, M. (J. Am. Chem. Soc., 2017)

(untitled) - Wilhelm, S.; Tavares, A. J.; Dai, Q.; Ohta, S.; Audet, J.; Dvorak, H. F.; Chan, W. C. W. (Nat. Rev. Mater., 2016)

(untitled) - Chuard, N.; Fujisawa, K.; Morelli, P.; Saarbach, J.; Winssinger, N.; Metrangolo, P.; Resnati, G.; Sakai, N.; Matile, S. (J. Am. Chem. Soc., 2016)

(untitled) - Sakai, N.; Matile, S. (J. Am. Chem. Soc., 2003)

(untitled) - Schmuck, C. (Coord. Chem. Rev., 2006)

(untitled) - Schmuck, C. (Chem. Commun., 1999)

(untitled) - Blondeau, P.; Segura, M.; Pérez-Fernández, R.; de Mendoza, J. (Chem. Soc. Rev., 2007)

(untitled) - Schmuck, C. (Chem. – Eur. J., 2000)

(untitled) - Li, M.; Mosel, S.; Knauer, S. K.; Schmuck, C. (Org. Biomol. Chem., 2018)

(untitled) - Li, M.; Schlesiger, S.; Knauer, S. K.; Schmuck, C. (Angew. Chem., Int. Ed., 2015)

(untitled) - Vermeulen, L. M. P.; De Smedt, S. C.; Remaut, K.; Braeckmans, K. (Eur. J. Pharm. Biopharm., 2018)

(untitled) - Jiang, H.; Hu, X.-Y.; Mosel, S.; Knauer, S. K.; Hirschhäuser, C.; Schmuck, C. (ChemBioChem, 2019)

(untitled) - Kuchelmeister, H. Y.; Gutschmidt, A.; Tillmann, S.; Knauer, S.; Schmuck, C. (Chem. Sci., 2012)

(untitled) - Junghänel, S.; Karczewski, S.; Bäcker, S.; Knauer, S. K.; Schmuck, C. (ChemBioChem, 2017)

(untitled) - Samanta, K.; Jana, P.; Bäcker, S.; Knauer, S.; Schmuck, C. (Chem. Commun., 2016)

(untitled) - Jana, P.; Samanta, K.; Bäcker, S.; Zellermann, E.; Knauer, S.; Schmuck, C. (Angew. Chem., Int. Ed., 2017)

(untitled) - Hu, X.-Y.; Ehlers, M.; Wang, T.; Zellermann, E.; Mosel, S.; Jiang, H.; Ostwaldt, J.-E.; Knauer, S. K.; Wang, L.; Schmuck, C. (Chem. – Eur. J., 2018)

(untitled) - Kuchelmeister, H. Y.; Karczewski, S.; Gutschmidt, A.; Knauer, S.; Schmuck, C. (Angew. Chem., Int. Ed., 2013)

(untitled) - Li, M.; Ehlers, M.; Schlesiger, S.; Zellermann, E.; Knauer, S. K.; Schmuck, C. (Angew. Chem., Int. Ed., 2016)

(untitled) - Bang, E.-K.; Gasparini, G.; Molinard, G.; Roux, A.; Sakai, N.; Matile, S. (J. Am. Chem. Soc., 2013)

(untitled) - Gasparini, G.; Bang, E.-K.; Molinard, G.; Tulumello, D. V.; Ward, S.; Kelley, S. O.; Roux, A.; Sakai, N.; Matile, S. (J. Am. Chem. Soc., 2014)

(untitled) - Zhou, J.; Sun, L.; Wang, L.; Liu, Y.; Li, J.; Li, J.; Li, J.; Yang, H. (Angew. Chem., Int. Ed., 2019)

(untitled) - Lu, J.; Wang, H.; Tian, Z.; Hou, Y.; Lu, H. (J. Am. Chem. Soc., 2020)

(untitled) - Liu, Y.; Jia, Y.; Wu, Q.; Moore, J. S. (J. Am. Chem. Soc., 2019)

(untitled) - Deng, Y.; Zhang, Q.; Feringa, B. L.; Tian, H.; Qu, D.-H. (Angew. Chem., Int. Ed., 2020)

(untitled) - Zhang, X.; Waymouth, R. M. (J. Am. Chem. Soc., 2017)

(untitled) - Yuan, P.; Mao, X.; Wu, X.; Liew, S. S.; Li, L.; Yao, S. Q. (Angew. Chem., Int. Ed., 2019)

(untitled) - Kichler, A.; Remy, J. S.; Boussif, O.; Frisch, B.; Boeckler, C.; Behr, J. P.; Schuber, F. (Biochem. Biophys. Res. Commun., 1995)

(untitled) - Fu, J.; Yu, C.; Li, L.; Yao, S. Q. (J. Am. Chem. Soc., 2015)

(untitled) - Meng, X.; Li, T.; Zhao, Y.; Wu, C. (ACS Chem. Biol., 2018)

(untitled) - Shu, Z.; Tanaka, I.; Ota, A.; Fushihara, D.; Abe, N.; Kawaguchi, S.; Nakamoto, K.; Tomoike, F.; Tada, S.; Ito, Y.; Kimura, Y.; Abe, H. (Angew. Chem., Int. Ed., 2019)

(untitled) - Torres, A. G.; Gait, M. J. (Trends Biotechnol., 2012)

(untitled) - Oupický, D.; Li, J. (Macromol. Biosci., 2014)

(untitled) - Gasparini, G.; Sargsyan, G.; Bang, E.-K.; Sakai, N.; Matile, S. (Angew. Chem., Int. Ed., 2015)

(untitled) - Zong, L.; Bartolami, E.; Abegg, D.; Adibekian, A.; Sakai, N.; Matile, S. (ACS Cent. Sci., 2017)

(untitled) - Chuard, N.; Poblador-Bahamonde, A. I.; Zong, L.; Bartolami, E.; Hildebrandt, J.; Weigand, W.; Sakai, N.; Matile, S. (Chem. Sci., 2018)

(untitled) - Cheng, Y.; Zong, L.; López‐Andarias, J.; Bartolami, E.; Okamoto, Y.; Ward, T. R.; Sakai, N.; Matile, S. (Angew. Chem., Int. Ed., 2019)

(untitled) - Peraro, L.; Deprey, K. L.; Moser, M. K.; Zou, Z.; Ball, H. L.; Levine, B.; Kritzer, J. A. (J. Am. Chem. Soc., 2018)

(untitled) - Moreau, D.; Gruenberg, J. (Chimia, 2016)

(untitled) - Abraham, V. C.; Taylor, D. L.; Haskins, J. R. (Trends Biotechnol., 2004)

(untitled) - Eggert, U. S.; Mitchison, T. J. (Curr. Opin. Chem. Biol., 2006)

(untitled) - López-Andarias, J.; Saarbach, J.; Moreau, D.; Cheng, Y.; Derivery, E.; Laurent, Q.; González-Gaitán, M.; Winssinger, N.; Sakai, N.; Matile, S. (J. Am. Chem. Soc., 2020)

(untitled) - Rinkenauer, A. C.; Vollrath, A.; Schallon, A.; Tauhardt, L.; Kempe, K.; Schubert, S.; Fischer, D.; Schubert, U. S. (ACS Comb. Sci., 2013)

(untitled) - Laurent, Q.; Sakai, N.; Matile, S. (Helv. Chim. Acta, 2019)

(untitled) - Deprey, K.; Kritzer, J. A. (Methods Enzymol., 2020)

(untitled) - Liss, V.; Barlag, B.; Nietschke, M.; Hensel, M. (Sci. Rep., 2016)